Digital Interventions to Save Lives From the Opioid Crisis Prior and During the SARS COVID-19 Pandemic: A Scoping Review of Australian and Canadian Experiences - Andrea Donnell; Chandana Unnithan; Jessica Tyndall; Fahad Hanna (Frontiers Media S.A., 2022)
BackgroundThe potential for digital initiatives for opioid harm reduction is boundless. Synthesized evidence on current interventions and their efficacy are emerging. This scoping review is an effort to aggregate Canadian and Australian digital health initiatives used to prevent opioid-related deaths and minimize harm, prior to and particularly during the pandemic of SARs-COVID-19, when the crisis escalated.MethodsThe Joanna Briggs Institute's methodological framework for conducting scoping reviews was used. Peer reviewed and gray literature published between January 2016 to October 2021 were included. Search translation was performed across CINAHL, Cochrane, SCOPUS, MEDLINE Complete, and ProQuest Public Health with consistent use of key search terms. Citation checks were also conducted. Studies included were written in English and reported on digital technologies to prevent opioid-related harm and/or mortality in participants aged 18 years or older in Australia and Canada.ResultsA total of 16 publications were included in the final analysis (Australia = 5; Canada = 11). The most frequently reported digital technologies were telehealth to support access to treatment (n = 3) and mobile applications for overdose monitoring and prevention (n = 3). Telehealth-delivered opioid replacement therapy demonstrated equal outcomes and treatment retention rates compared to in-person and mobile applications for overdose monitoring demonstrated lifesaving capability through direct linkages with emergency response services.ConclusionsDigital interventions to minimize opioid crisis related harm and overdose prevention are fast emerging in Australia and Canada. During the pandemic, the crisis escalated in both countries as a public health emergency, and different initiatives were trialed. Digital harm reduction solutions via mobile apps (or SaaS solutions) were found to have the potential to prevent accidental overdose deaths and save lives, if rendered through privacy preserved, secure and trust enabled methods that empower users. Knowledge sharing between the two countries, relating to suitable interventions, may add significant value in combatting the escalating opioid crisis in the post pandemic era.